Design processes for electronic books - Brunát, Tomáš; Říhová, Zora, 1948-; Drongová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
The thesis is engaged in the modeling of business processes, focusing on their design development, namely processes related to publishing electronic books. The main goal of the thesis is application of the EPC process modeling method for selected processes in a particular company Grada Publishing, a.s. The theoretical part is focused on process description, optimization, management and process modeling standards. The practical part is devoted to design development of the processes related to publishing e books under the EPC standards. Each process is described and if it was necessary to show more details of it, also other specifications were added. Once the process was developed, a theoretical optimization of its sales related sub process was designed proposed.
Vedoucí práce: Zora Říhová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses